2008
DOI: 10.1111/j.1751-7133.2008.07569.x
|View full text |Cite
|
Sign up to set email alerts
|

Admission Hyperglycemia and Length of Hospital Stay in Patients With Diabetes and Heart Failure: A Prospective Cohort Study

Abstract: The authors assessed the relationship between glycemia and length of hospital stay (LOS) in a prospective cohort study of patients with diabetes mellitus and heart failure (HF). Of 212 patients with acute HF exacerbation, 119 (56%) also had diabetes. The mean age of the cohort was 63+/-0.87 years, and the mean body mass index was 29.3 kg/m2. Diabetic patients had significantly longer LOS compared with the nondiabetics (5.0+/-0.29 vs 3.4+/-0.19; P<.001). In patients with diabetes, the mean glycated hemoglobin A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
8
0
5
Order By: Relevance
“…In our cohort, diabetes was associated with worse event-free survival and mortality. It is known that patients with diabetes are more likely to have heart failure [30] and have prolonged hospital length of stay when admitted for acute heart failure exacerbation [31].…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, diabetes was associated with worse event-free survival and mortality. It is known that patients with diabetes are more likely to have heart failure [30] and have prolonged hospital length of stay when admitted for acute heart failure exacerbation [31].…”
Section: Discussionmentioning
confidence: 99%
“…Previous randomized controlled studies, albeit in non-COVID-19 patients, have shown a strong association between better glycemic control during the first days of hospitalization and better outcomes in patients admitted to the ICU, surgical, or medical wards. 23 , 24 , 25 A recent study examined the temporality of the association between poor glucose control on admission and throughout the first few days of hospitalization and the outcomes of COVID-19 and found a seven fold increase in mortality risk in patients with COVID-19 and severe hyperglycemia. 26 These findings highlight the importance of maintaining well-controlled glucose in patients with COVID-19 and call for the implementation of glucose management protocols such as ours to help health care providers, caring for patients with COVID-19 and dexamethasone-induced hyperglycemia, accomplish this goal as early as possible during the patient’s hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reflect the impact of hyperglycemia and patient outcomes. Gebreegziabher et al [11] conducted a prospective cohort study addressing glycaemia and length of hospital stay (LOS) in patients admitted for acute heart failure exacerbation. A significantly longer LOS was noted in patients with DM as compared with patients without diabetes (5.0 ± 0.29 vs 3.4 ± 0.19; p < .001).…”
Section: Discussionmentioning
confidence: 99%